Hepatic Inflammation Confers Protective Immunity Against Liver Stages of Malaria Parasite - Grand, Morgane; Waqasi, Mishelle; Demarta-Gatsi, Claudia; Wei, Yu; Peronet, Roger; Commere, Pierre-Henri; Puig, Amandine; Axelrod, Jonathan; Caldelari, Reto; Heussler, Volker; Amino, Rogerio; Mecheri, Salaheddine (Frontiers in Immunology, 2020)
The mechanisms by which Plasmodium parasites develop inside hepatocytes are important steps toward the understanding of malaria pathogenesis. We propose that the nature and the magnitude of the inflammatory response in the liver are key for the establishment of the infection. Here, we used mice deficient in the multidrug resistance-2 gene (Mdr2-/-)-encoded phospholipid flippase leading to the development of liver inflammation. Infection of Mdr2-/- mice with Plasmodium berghei ANKA (PbANKA) sporozoites (SPZ) resulted in the blockade of hepatic exo-erythrocytic forms (EEFs) with no further development into blood stage parasites. Interestingly, cultured primary hepatocytes from mutant and wild-type mice are equally effective in supporting EEF development. The abortive infection resulted in a long-lasting immunity in Mdr2-/- mice against infectious SPZ where neutrophils and IL-6 appear as key effector components along with CD8+ and CD4+ effector and central memory T cells. Inflammation-induced breakdown of liver tolerance promotes anti-parasite immunity and provides new approaches for the treatment of malaria infections.